Pristine-state structure of lithium-ion-battery cathode material Li1.2Mn0.4Co0.4O2 derived from NMR bond pathway analysis. Issue 21 (7th June 2015) - Iddir, Hakim; Key, Baris; Dogan, Fulya; Russell, John T.; Long, Brandon R.; Bareño, Javier; Croy, Jason R.; Benedek, Roy
<x xml:space="preserve">Abstract</x> Layered lithium ion battery cathode materials have been extensively investigated, of which layered–layered composites xLi2MnO3·(1 − x)LiMO2 (M = Mn, Co, Ni) are of particular interest, owing to their high energy density.